Respuesta :

The answer is v = 15z - pz

Ver imagen laurentspencer319

The equation in terms of v is [tex]v = z(15-p)[/tex]

Given that,

Equation; 6z + 9z = pz + v

We have to determine,

Solve the equation for v.

According to the question,

To determine the value of v follow all the steps given below.

Equation; [tex]6z + 9z = pz + v[/tex]

  • Step1; Adding 6z and 9z both the terms it become equal to 15z.

          [tex]6z + 9z = pz + v\\\\15z = pz + v[/tex]

  • Step2; Take the term pz to right hand side .

            [tex]15z - pz = v[/tex]

  • Step3; There is common factor is z taking common z from right hand side.

           [tex]z (16-p)= v[/tex]

  • Step4; The equation represented in terms of v.

            [tex]v = z (15-p)[/tex]

Hence, The equation in terms of v is [tex]v = z(15-p)[/tex].

To know more about the Equation click the link given below.

https://brainly.com/question/14484294

ACCESS MORE